The Mediterranean and Nordic Diet: A Review of Differences and Similarities of Two Sustainable, Health-Promoting Dietary Patterns - Krznarić, Željko; Karas, Irena; Ljubas Kelečić, Dina; Vranešić Bender, Darija (Frontiers in Nutrition, 2021)
The Mediterranean diet (MD) and the Nordic diet (ND) share more similarities than differences. Both diets are based on typical local and seasonal foods, share similar nutritional recommendations based on plant-based dietary principles, and are both now orienting towards environmental protection and sustainability. The main difference between the two diets is the primary fat source. Olive oil is the synonym for MD while the ND uses more rapeseed/canola oil. While longitudinal epidemiological studies support adherence to MD as a way to prevent chronic diseases, ND still needs more such studies because the current results are discrepant. Notably, studies that assessed association between both diets and lower risks of chronic diseases, disability, mortality from specific and all causes, implied that ND could also have an advantageous effect as MD. Hopefully, there will be more longitudinal and large prospective studies in the future that will provide more evidence-based recommendations.